Feasibility of a magazine on the circulatory system based on an inventory of medicinal plants - Ananda Dwi Putri; Ruqiah Ganda Putri Panjaitan; Eko Sri Wahyuni (University of Muhammadiyah Malang, 2025)
Learning is a continuous process involving teachers, students, materials, and the environment to achieve specific goals. One important aspect of learning is the use of learning media. This study develops a learning media in the form of a magazine on the human circulatory system and an inventory of antihypertensive medicinal plants in Sari Makmur Village, Tekarang District, Sambas Regency. The magazine aims to enhance students' understanding and awareness of the potential of their surrounding environment. This study aims to evaluate the feasibility of the magazine as a learning media. The method used is research and development (R&D) with a qualitative approach, referring to Sugiyono's model, which includes five stages: identification of potential and problems, data collection, product design, design validation, and design revision. The validation of the magazine was carried out by five biology and learning media experts, based on aspects of presentation, content, and language. The results of the validation using the Content Validity Ratio (CVR) and Content Validity Index (CVI) showed a value of 1.00 in all aspects. The reliability test with the Intraclass Correlation Coefficient (ICC) yielded a value of 0.841, which is categorized as excellent. Therefore, the developed magazine is declared valid and feasible to be used as a learning media.